Elucidation of haem‐binding sites in the actinobacterial protein HbpS. Issue 2 (21st February 2013) - Torda, Andrew E.; Groves, Matthew R.; Wedderhoff, Ina; Ortiz de Orué Lucana, Darío
Abstract The extracellular haem‐binding protein from Streptomyces reticuli (HbpS) has been shown to be involved in redox sensing and to bind haem. However, the residues involved in haem coordination are unknown. Structural alignments to distantly related haem‐binding proteins from Mycobacterium tuberculosis were used to identify a candidate haem‐coordinating residue, and site‐directed mutagenesis with UV/Vis spectroscopy was used to assess haem binding in vivo and in vitro. We present strong evidence that HbpS belongs to the small set of proteins, which do not use histidine to coordinate the metal in the haem group. Further spectroscopic evidence strongly indicates that threonine 113 is actively involved in coordination of haem. Subsequent protein/haem titration experiments show a 1 : 2, protein/haem stoichiometry. We also present data showing the degradation of haem by HbpS in vivo. Because HbpS is conserved in many Actinobacteria, the presented results are applicable to related species.